Exploring the net impact of internet business solution adoption on SME performance. (9th November 2004) - Wade, Michael; Johnston, David; McClean, Ron
This study explores the post-adoption effect of internet business solutions (IBS) on business value creation, as measured by firm revenues, direct and indirect costs, and investment satisfaction for a sample of 254 small- and medium-sized enterprises (SMEs). In addition, the study tests how well the much-discussed Revolutionary and Evolutionary views of e-business strategy fit the data. The results of the study show that business value can be significantly enhanced by the adoption of internet business solutions. Furthermore, benefits are not mutually exclusive to either view – the surveyed organisations experienced post-IBS adoption benefits by pursuing both strategies concurrently.